SENSORS FOR DETERMINING MICROCLIMATES IN FRUIT AND VEGETABLE STORAGE FACILITIES - Norqulova, F.N. (SCIENCE and SOCIETY, 2025)
This article explores the role of advanced sensors in monitoring and regulating essential environmental parameters such as temperature, humidity, carbon dioxide, oxygen, and ethylene levels. By integrating IoT technology, these sensors enable real-time data collection, remote monitoring, and automated control systems to ensure the quality and longevity of stored produce.